2002
DOI: 10.1046/j.1365-2699.2002.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical abundance distributions of coastal invertebrates: using one‐dimensional ranges to test biogeographic hypotheses

Abstract: Aim It is often assumed that species generally reach their highest densities in the centre of their range and decline in abundance towards the range edges. A number of mechanisms have been proposed that could theoretically support this pattern, and several ecological theories have been developed based on the assumption that this pattern occurs in nature. However, few studies have quantified geographical patterns of species abundance throughout species ranges. This is largely because of the logistical challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
179
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(197 citation statements)
references
References 40 publications
13
179
5
Order By: Relevance
“…Although all three study species have planktonic larvae that spend up to a few weeks in the water column (Wisely and Blick 1964;Underwood 1974;Caffey 1985), recent genetic investigations into the connectivity of populations of rocky, intertidal marine species across the Ninety Mile Beach biogeographical barrier have revealed that degree of population connectivity across this barrier is not related to the mode of larval dispersal, but rather, to flexibility in habitat utilisation (Ayre et al 2009). The present study supports the mounting evidence (Sagarin and Gaines 2002b;Gilman 2005;Sagarin et al 2006) that the abundant-centre hypothesis is too simplistic a model to predict the abundance distributions of planktonically developing benthic marine invertebrates. Our results indicate that abundances of rocky-shore, intertidal invertebrate species are highly variable and perhaps unpredictable across the range, and that their recruitment can be extremely patchy and episodic.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Although all three study species have planktonic larvae that spend up to a few weeks in the water column (Wisely and Blick 1964;Underwood 1974;Caffey 1985), recent genetic investigations into the connectivity of populations of rocky, intertidal marine species across the Ninety Mile Beach biogeographical barrier have revealed that degree of population connectivity across this barrier is not related to the mode of larval dispersal, but rather, to flexibility in habitat utilisation (Ayre et al 2009). The present study supports the mounting evidence (Sagarin and Gaines 2002b;Gilman 2005;Sagarin et al 2006) that the abundant-centre hypothesis is too simplistic a model to predict the abundance distributions of planktonically developing benthic marine invertebrates. Our results indicate that abundances of rocky-shore, intertidal invertebrate species are highly variable and perhaps unpredictable across the range, and that their recruitment can be extremely patchy and episodic.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, the predictability of the abundances of each species varied with scale at which the abundance was assessed. Sagarin and Gaines (2002b) and Gilman (2005) found similarly large variations in the large-and small-scale patterns of abundance along the geographical ranges of 13 rocky-shore, intertidal marine invertebrates on the western coast of the USA.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…ignoring other spatial variation), density does not peak in the centre, but rather is the highest close to the coastal margin, declining inland up to approximately 200 m. For an island of this overall, elliptical shape and with a considerable change in elevation, a central peak in abundance might be expected to take a torus-like form, but this was clearly not the case for D. panormitanum. Complex abundance structures are now considered the norm rather than the exception, with little evidence for an 'abundant centre distribution' either across entire ranges or partial components thereof (Brewer & Gaston 2002;Sagarin & Gaines 2002b;Gaston 2003;McGeoch & Price 2004;Sagarin et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Because species are usually distributed over large areas latitudinally, species range limits are most often studied on a broad geographic scale (e.g., Sagarin and Gaines 2002;Sorte and Hofmann 2004;Kuo and Sanford 2009). Such studies have been important for identifying potential biotic and abiotic limiting factors for a host of different species and their potential adaptations at range edges (e.g., Fawcett 1984;Zacherl et al 2003;Lima et al 2007; reviewed by Bridle and Vines 2007;Sexton et al 2009).…”
Section: Introductionmentioning
confidence: 99%